1997
DOI: 10.1128/mcb.17.5.2920
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimerization of Msx and Dlx Homeoproteins Results in Functional Antagonism

Abstract: It is widely accepted that the specific actions of transcriptional regulatory proteins are mediated through their selective association with other protein factors. Such interactions allow transcription factors to distinguish relevant target sequences from the many fortuitous binding sites in the genome and confer highly precise transcriptional regulatory properties. Selective protein-protein interactions are thought to be particularly important for specifying the actions of homeodomaincontaining transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
199
1
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(213 citation statements)
references
References 42 publications
12
199
1
1
Order By: Relevance
“…Similar regulation models have been proposed in various transcription factor families. Indeed, for example, Msx and D1x homeoproteins, which exhibit overlapping expression patterns, form heterodimers with respect to their functional antagonism (Zhang et al, 1997). Moreover, TBP dimerization have been shown to inhibit DNA-binding and, consequently, to provide a mode of regulating TBP-DNA interaction (Taggart and Pugh, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Similar regulation models have been proposed in various transcription factor families. Indeed, for example, Msx and D1x homeoproteins, which exhibit overlapping expression patterns, form heterodimers with respect to their functional antagonism (Zhang et al, 1997). Moreover, TBP dimerization have been shown to inhibit DNA-binding and, consequently, to provide a mode of regulating TBP-DNA interaction (Taggart and Pugh, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that Msx2 is a transcriptional repressor that acts as a functional antagonist to Dlx5-induced osteogenesis. [19][20][21][22][23] Studies have shown that Msx2 and Dlx5 act in reciprocal manners with regard to the regulation of osteogenesis and expression of alkaline phosphatase and osteocalcin. [19][20][21][22][23] While Dlx5 promotes osteogenesis and expression of alkaline phosphatase and osteocalcin, Msx2 represses these activities.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] Studies have shown that Msx2 and Dlx5 act in reciprocal manners with regard to the regulation of osteogenesis and expression of alkaline phosphatase and osteocalcin. [19][20][21][22][23] While Dlx5 promotes osteogenesis and expression of alkaline phosphatase and osteocalcin, Msx2 represses these activities. [19][20][21][22][23] This may explain why PMMA particles inhibited the expression of Dlx5 but not of Msx2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These presumably regulate chondrocyte cell cycle progression through modulation of activity of cyclins/cdk kinases, as well as the exit from the cell cycle in the progression to hypertrophy. Further, the transcription factors AP1 (jun/fos: Wang et al, 1992;Watanabe et al, 1997), ATF2 (Reimold et al, 1996), Cbfa1 (Ducy and Karsenty, 1998;Inada et al, 1999;Kim et al, 1999;Komori et al, 1997), RARα (Cash et al, 1997;Yamaguchi et al, 1998), Gli2 and Gli3 (Mo et al, 1997), Prx1 and Prx2 (Lu et al, 1999), Dlx5 (Ferrari et al, 1995), Msx2 (Ferrari et al, 1998;Marazzi et al, 1997;Zhang et al, 1997b) and Hox transcription factors (see below) influence the propensity of chondrocytes to differentiate and mature.…”
Section: Local Control Of Bone Shape During Embryogenesis and Growthmentioning
confidence: 99%